2018
DOI: 10.1002/brb3.904
|View full text |Cite
|
Sign up to set email alerts
|

Impulse control disorders in Parkinson's: Sleep disorders and nondopaminergic associations

Abstract: ObjectivesImpulse control disorders (ICDs) are common among patients with Parkinson's disease (PD). Risk factors identified for developing ICDs include young age, family history, and impulsive personality traits. However, the association of these potentially disabling disorders with nondopaminergic drugs and sleep disorders has been understudied. Our objective was to examine the association between ICDs and nondopaminergic medications and sleep disorders.MethodsWe conducted an observational study of 53 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 36 publications
0
8
0
1
Order By: Relevance
“…Long-term treatment with some of these medications, such as antidepressants, has been associated with overactivity of dopaminergic neuropathways (77). One study found that after accounting for possible confounding variables including motor score, age, gender, and disease duration, antidepressants were significantly associated with total impulsivity score, and sleep inducers were significantly associated with a binge eating impulsivity subscore (78). Few case reports have reported non-dopaminergic medications inducing ICDs in PD (79).…”
Section: Medication and Surgical Associationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Long-term treatment with some of these medications, such as antidepressants, has been associated with overactivity of dopaminergic neuropathways (77). One study found that after accounting for possible confounding variables including motor score, age, gender, and disease duration, antidepressants were significantly associated with total impulsivity score, and sleep inducers were significantly associated with a binge eating impulsivity subscore (78). Few case reports have reported non-dopaminergic medications inducing ICDs in PD (79).…”
Section: Medication and Surgical Associationsmentioning
confidence: 99%
“…Sleep disorders have also been investigated, with some studies finding more sleep impairment and daytime sleepiness in PD patients with ICDs (5, 65). Although some studies that defined sleep disorders through questionnaires found an association with ICDs, more recent studies—including those that have screened sleep disorders through polysomnography exams—have revealed inconsistent results (15, 78, 143, 144). Patients with ICDs may also have more restless leg syndrome (65).…”
Section: Premorbidities and Comorbiditiesmentioning
confidence: 99%
“…The frequency of ICD in de novo PD patients is similar to the general population (5), but numerous studies reported higher frequency during the course of the disease (8)(9)(10)(11)(12). Treatment by dopamine agonists (DA), mainly through stimulation of the D3-receptor (13) has been proposed as a causal factor.…”
Section: Introductionmentioning
confidence: 99%
“…Antidepressants and sleep inducers are also significant predictors for individual ICD ( 35 ). Aripiprazole, an antipsychotic drug with partial dopamine agonist properties, has been reported to be associated with ICDs especially pathological gambling ( 36 ).…”
Section: The Risk Factors Of Icdsmentioning
confidence: 99%